Academic Culture, Leadership, and Islamic Motivation as Predictors of Lecturer Performance: Evidence from an Indonesian Pesantren - Sari, Ahmad Fitriyadi; Ilzamudin, Ilzamudin; Sirojuddin, Rumbang; Rahmatullah, Mamat (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study examines the influence of academic culture, transformational leadership, and Islamic work motivation on Lecturer Performance at Darunna'im Islamic Boarding School (Sekolah Tinggi Pesantren Darunna'im, STPDN) Rangkasbitung. A quantitative approach was employed, using a structured questionnaire for data collection. The data were analyzed using descriptive statistics and hypothesis testing with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The respondents consisted of lecturers at Darunna'im Islamic Boarding School. The results revealed that academic culture significantly and positively influenced Lecturer Performance (path coefficient = 0.301). Transformational leadership also had a strong positive effect (0.572), while Islamic work motivation showed a smaller yet significant positive influence (0.087). These findings highlight the importance of fostering a supportive academic culture, effective leadership, and religiously driven motivation in enhancing Lecturer Performance. The results offer valuable insights for Islamic educational institutions to formulate strategic policies to improve educational quality and institutional reputation.